How transmembrane peptides insert and orientate in biomembranes: a combined experimental and simulation study. Issue 26 (15th June 2016) - Yue, Tongtao; Sun, Mingbin; Zhang, Shuai; Ren, Hao; Ge, Baosheng; Huang, Fang
Abstract : After the synthesis of transmembrane peptides/proteins (TMPs), their insertion into a lipid bilayer is a fundamental biophysical process. Abstract : After the synthesis of transmembrane peptides/proteins (TMPs), their insertion into a lipid bilayer is a fundamental biophysical process. Moreover, correct orientations of TMPs in membranes determine the normal functions they play in relevant cellular activities. In this study, we have established a method to determine the orientation of TMPs in membranes. This method is based on the use of TAMRA, a fluorescent molecule with high extinction coefficient and fluorescence quantum yield, to act as a fluorescent probe and tryptophan as a quencher. Fluorescence quenching indicates that the model peptide displays membrane orientation with the N terminus outside and the C terminus inside dominantly. To elucidate the underlying mechanism, we performed molecular dynamics simulations. Our simulations suggest that both membrane insertion and the orientation of TMPs are determined by complex competition and cooperation between hydrophobic and electrostatic interactions. After initial membrane anchorage via electrostatic interactions of the charged residues with the lipid headgroups, further insertion is hindered by unfavorable interactions between the polar residues and lipid tails, which result in an energy barrier. Nevertheless, such a finite energy barrier is reduced by hydrophobic interactions between the non-polar residues and lipid tails. Moreover, a transient terminal flipping was captured to facilitate the membrane insertion. Once the inserted terminus reaches the opposite lipid headgroups, the hydrophobic interactions cooperate with the electrostatic interactions to complete the membrane insertion process.